Partially-constrained sex allocation and the indirect effects of assisted reproductive technologies on the human sex ratio - Hardy, Ian C.W.; Maalouf, Walid E. (Cambridge University Press, 2016)
Infertility affects around 15% of human couples and in many countries approximately 1–4% of babies are born following Assisted Reproductive Technologies (ART). Several ART techniques are used and these differentially affect the sex ratio of offspring successfully produced. These direct effects on sex ratio also have the potential to influence, indirectly, the sex ratios of offspring born to untreated couples. This is of concern because human sex ratio bias may adversely affect public health. Here the extent of indirect effects of ART that could operate, via Fisherian frequency-dependent natural selection, on the progeny sex ratio of unassisted members of a population is heuristically modelled. Given the degrees to which ART techniques bias sex ratios directly, it is predicted that well over 20% of couples would have to reproduce via ART for there to be any discernible effect on the sex ratios produced, in response, by the remainder of the population. This value is greater than the estimated prevalence of infertility problems among human couples. It is concluded that providing ART to couples with fertility problems does not currently generate significant ethical issues or public health concern in terms of indirect effects on the offspring sex ratios of untreated couples.